Mechanical Forcing of Convection by Cold Pools: Collisions and Energy Scaling. (22nd November 2020) - Meyer, Bettina; Haerter, Jan O.
Abstract: Forced mechanical lifting through cold pool gust fronts can trigger new convection and, as previous work highlights, is enhanced when cold pools collide. However, as shown by conceptual models, the organization of the convective cloud field emerging from two versus three colliding cold pools differs strongly. In idealized dry large‐eddy simulations we therefore compare collisions between two and three cold pools. The triggering likelihood is quantified in terms of the cumulative vertical mass flux of boundary layer air and the instantaneous updraft strength, generated at the cold pool gust fronts. We find that cold pool expansion can be well described by initial potential energy alone. Cold pool expansion monotonically slows but shows an abrupt transition between an axisymmetric and a broken‐symmetric state mirrored by a sudden drop in expansion speed. We characterize these two dynamic regimes by two distinct power law exponents and explain the transition by the onset of "lobe‐and‐cleft" instabilities at the cold pool head. Two‐cold pool collisions produce the strongest instantaneous updrafts in the lower boundary layer, which we expect to be important in environments with strong convective inhibition. Three‐cold pool collisions generate weaker but deeper updrafts and the strongest cumulative mass flux and are thus predicted to induce the largest midlevel moistening, which has been identified as a precursor for the transition from shallow to deep convection. Combined, our findings may help decipher the role of cold pools in spatially organizing convection and precipitation. Plain Language Summary: The arrival of a convective thunderstorm is often announced by strong and cold wind gusts that can be felt by an observer at the surface. These gust fronts constitute the outer edge of cold pools, which are formed underneath clouds when part of the rain reevaporates before reaching the surface, thereby cooling the air. These cold pools have received increasing attention due to their contribution in the generation of new convective rain events, thereby affecting the spatial pattern of the cloud field. In this study we use a high‐resolution numerical model to study the life cycle of single cold pools and their collision with other cold pools. We assume that the likelihood that a cold pool causes a new rain event depends on (i) the vertical velocity of the wind gusts produced at its gust front and where it collides and (ii) how much moisture it can transport upward to a height where the water condenses and forms clouds. We show that both these factors are strongly increased where two or more cold pools collide, highlighting the importance of the representation of cold pool collisions in climate models to achieve a more realistic representation of clouds and rain. Key Points: A cold pool's initial potential energy is a good predictor of its spreading dynamics Cold pool radii evolve as a combinationof two power laws, highlighting a dynamic transition induced by "lobe‐and‐cleft" instabilities Updrafts and mass flux are strongly enhanced in multicold pool collisions compared to single cold pool gust fronts.